Nutrient Accumulation in the Sediment of Silvofishery Ponds in Semarang - Hastuti, Endah Dwi; Budihastuti, Rini (Makara Journal of Science, 2017)
Information concerning the functionality of mangrove within silvofishery ponds is needed, especially relating to the accumulation rate of organic materials and nutrients. This research studied the effect of mangrove structure on the accumulation rate of nutrients within silvifishery ponds. The research, conducted in May 2016, used canals of width 1, 2, and 3 m, with mangrove species Avicennia marina and Rhizophora mucronata, alone or in combination. Nutrients measured were nitrogen, phosphorus and organic matter, in the sediment of the treatment ponds, through soil sampling followed by laboratory analysis. The respective analysis methods used were Kjehdahl, spectrophotometry, and ashing. Data analysis was conducted using factorial ANOVA. The highest nitrogen concentration was detected in the treatment with 15 stands of mixed mangrove species (0.63 ± 0.04 %), the treatment with 10 stands of mixed mangroves showed the highest phosphorus concentration (62.86 ± 12.31 mg/kg), and the highest organic matter concentration (2.55 ± 0.67 %) was seen with 10 stands of R. mucronata. The highest average value based on partial group showed that R. mucronata had the highest nitrogen accumulation at 0.56 ± 0.07 %; for phosphorus, the mixed species pond (62.02 ± 7.84 mg/kg); and for organic matter, R. mucronata (2.41 ± 0.39 %).